Forward genetics in clostridial acetogens as a route to process improvements - Woods, Craig Alexander (2018)
Clostridium autoethanogenum is able to use CO or CO2 + H2 as a sole carbon and energy source and natively produces the industrially relevant compounds ethanol, 2,3-butanediol and acetate. Increasing concerns about energy security, environmental impacts of fossil fuel usage and long term fuel and chemical production have led to the commercialisation of biological production of fuels and chemicals. C. autoethanogenum has been adopted as the organism of choice by a leading biotechnology company which has now reached full commercial-scale ethanol production using industrial waste gases as feedstock in a process termed gas fermentation. Strain development is a crucial process to the further adoption of this gas fermentation technology. An important step in strain development is establishing reliable and efficient DNA transfer protocols. In this study a novel E. coli conjugal donor strain was constructed which offered up to 744-fold increases in conjugation efficiency over an established donor strain. Improvements in DNA transfer aided forward genetics using the mariner element himar1. Transposon mutants were identified including strains deficient in amino acid biosynthesis and motility as well as several mutants with significantly improved ethanol production. Transposon Directed Insertion-site Sequencing (TraDIS) involves the creation of a large transposon mutant pool followed by high-throughput sequencing to simultaneously map every insertion site. TraDIS is capable of producing a comprehensive list of candidate essential genes as well as gene targets implicated in product tolerance, as such it is a valuable tool for directing future strain engineering. Transposon-delivery vector and DNA sequencing library innovations have been demonstrated which will facilitate TraDIS experiments in this industrially important organism.